2023
DOI: 10.29219/fnr.v67.8991
|View full text |Cite
|
Sign up to set email alerts
|

Seed-derived peptide lunasin suppressed breast cancer cell growth by regulating inflammatory mediators, aromatase, and estrogen receptors

Abstract: Background: Breast cancer is one of the most prevalent cancers in women. Its pathology comprises tumor cells and nearby stromal cells, accompanied by cytokines and stimulated molecules, resulting in a favorable microenvironment for tumor progression. Lunasin is a seed peptide with multiple bioactivities derived from seeds. However, the chemopreventive effect of lunasin on different characteristics of breast cancer has not been fully explored. Objective: This study aims to explore the chemopreventive mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Leptin promotes cell proliferation and metastasis of 4T1 breast cancer cells; however, lunasin—a natural seed peptide first identified in soybeans—is able to inhibit metastasis by inhibiting the production of VEGF 53 . Moreover, lunasin inhibits breast cancer cell growth also by decreasing VEGF expression and leptin receptor mRNA expression 54 . The increased risk of breast cancer progression can be associated with the increased expression of proangiogenic factors, such as VEGF A, in THP‐1 macrophages stimulated by leptin synthesized in breast adipocytes 55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin promotes cell proliferation and metastasis of 4T1 breast cancer cells; however, lunasin—a natural seed peptide first identified in soybeans—is able to inhibit metastasis by inhibiting the production of VEGF 53 . Moreover, lunasin inhibits breast cancer cell growth also by decreasing VEGF expression and leptin receptor mRNA expression 54 . The increased risk of breast cancer progression can be associated with the increased expression of proangiogenic factors, such as VEGF A, in THP‐1 macrophages stimulated by leptin synthesized in breast adipocytes 55 .…”
Section: Resultsmentioning
confidence: 99%
“…53 Moreover, lunasin inhibits breast cancer cell growth also by decreasing VEGF expression and leptin receptor mRNA expression. 54 The increased risk of breast cancer progression can be associated with the increased expression of proangiogenic factors, such as VEGF A, in THP-1 macrophages stimulated by leptin synthesized in breast adipocytes. 55 Also, in a study on human leiomyoma cells, it was found that leptin treatment and adipocyte coculture increases the expression of angiogenic factors, VEGF in this range.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…IL-6 plays a crucial role in the tumor microenvironment [10], and it is the most abundant cytokine in this setting. Research results indicate that IL-6 is highly expressed 2 of 13 in almost all types of tumors. For instance, in a study involving 55 patients diagnosed with severe lung cancer, elevated IL-6 levels were found to be significantly associated with poorer performance status and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high IL-6 levels exhibited worse Eastern Cooperative Oncology Group scores and were more likely to experience disease progression [ 11 ]. The results of recent clinical studies have additionally shown that IL-6 levels are associated with clinical stage, poor prognosis, and survival in patients with various types of cancer, including cervical cancer [ 12 ], breast cancer [ 13 ], ovarian cancer [ 14 ], prostate cancer [ 15 ], and colorectal cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nontoxic chemopreventive potential of lunasin can be attributed to the 43 amino acid sequence's uniqueness, specifically the presence of a polyaspartyl end at the C-terminus [1] , a highly negatively charged domain with eight aspartic acid residues that appears to bind to deacetylated histones and inhibits mitosis [3,4] . Several studies have reported evidence of lunasin's in vitro and in vivo chemopreventive activity [5][6][7][8][9][10][11][12][13][14][15][16][17] . In the early 2000s, lunasin was purified, identified and quantified from different matrices using ionexchange column chromatography [18][19][20] , sodium dodecyl-sulfate polyacrylamide gel electrophoresis and western blot [18][19][20][21][22] .…”
mentioning
confidence: 99%